Uma proposta de plano de aula em educação financeira para o ensino médio - Salles, Marcelo Rodrigues (2018)
The main objective of this work is to contribute with the teaching of Financial Education, using research done in articles and other academic works, constituting material that shows how Financial Education has been approached in Brazil. At the end, a lesson plan, structured in the resolution of exercises, is proposed, addressing the concepts related to Financial Education and its application in people's daily lives. For this purpose, all the theoretical basis used for the development of the proposed questions was carried out, which sought to deal with real situations that can be applied in a simplified way in a high school class.